2021
DOI: 10.1111/pbi.13590
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐based discovery of maize transcription factors regulating male sterility and their functional conservation in plants

Abstract: Summary Identifying genic male‐sterility (GMS) genes and elucidating their roles are important to unveil plant male reproduction and promote their application in crop breeding. However, compared with Arabidopsis and rice, relatively fewer maize GMS genes have been discovered and little is known about their regulatory pathways underlying anther and pollen development. Here, by sequencing and analysing anther transcriptomes at 11 developmental stages in maize B73, Zheng58 and M6007 inbred lines, 1100 transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 76 publications
(117 reference statements)
2
73
0
Order By: Relevance
“…DNA sequencing of three target sites revealed that up to 84% of T 0 plants contained mutations in one site at least, while five plants generated from one event were homozygous triple mutants. We identified a homozygous loss-of-function triple mutant of ZmTGA9-1/-2/-3 with frameshift and truncation mutations from the five plants mentioned above (Figure S2A), including 1-bp deletion in ZmTGA9-1, and 1-bp insertion in ZmTGA9-2 and ZmTGA9-3, respectively (Figure 1(A2),B), which is a new allelic mutant differing from ZmTGA9 triple mutants obtained previously [10]. Since maize T 0 transgenic plants could not usually produce seeds by self-pollination in the greenhouse, we pollinated the T 0 plants with pollen grains from maize inbred line Zheng58, and then harvested F 1 seeds that could be divided into Cas9-positive (transgene) and Cas9-negative (non-transgene) segregation.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…DNA sequencing of three target sites revealed that up to 84% of T 0 plants contained mutations in one site at least, while five plants generated from one event were homozygous triple mutants. We identified a homozygous loss-of-function triple mutant of ZmTGA9-1/-2/-3 with frameshift and truncation mutations from the five plants mentioned above (Figure S2A), including 1-bp deletion in ZmTGA9-1, and 1-bp insertion in ZmTGA9-2 and ZmTGA9-3, respectively (Figure 1(A2),B), which is a new allelic mutant differing from ZmTGA9 triple mutants obtained previously [10]. Since maize T 0 transgenic plants could not usually produce seeds by self-pollination in the greenhouse, we pollinated the T 0 plants with pollen grains from maize inbred line Zheng58, and then harvested F 1 seeds that could be divided into Cas9-positive (transgene) and Cas9-negative (non-transgene) segregation.…”
Section: Resultsmentioning
confidence: 63%
“…However, only ZmTGA9-1, ZmTGA9-2, and ZmTGA9-3 are expressed during maize anther development based on RNA-seq data of W23 anther (Figure S1(A2)) [32], indicating the potentially critical roles of the three genes in controlling maize male reproduction. Based on co-introduced of two vectors containing Cas9 and sgRNA expression cassettes into maize, our previous research revealed that ZmTGA9 triple mutant displayed complete male sterility, while single and double mutants of ZmTGA9-1/-2/-3 showed normal fertility [10]. However, the co-transformation method influences transformation efficiency and especially increases the complexity of molecular identification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying genes by map-based cloning is time-consuming, and sometimes cloning of homologous genes is fast and effective. By analyzing the putative orthologs of GMS genes in Arabidopsis and rice, a putative regulatory network for anther and pollen development in maize was constructed (Wan et al, 2019;Jiang et al, 2021). In our study, DEGs/DEPs are involved in fatty acid biosynthesis process, lipid transport, L-phenylalanine metabolic process and polysaccharide metabolism in AL18A's anthers development (Figure 7).…”
Section: Genes Related To Anthers Development In Wheatmentioning
confidence: 96%
“…Anther development is one of the most critical events in the reproductive phase of plant development, involving hundreds of genes and proteins. Transcriptional factors (TFs) are the key connection points in regulatory networks associated with tapetal function and pollen development (Jiang et al, 2021). By comparing AL18A and AL18B, we analyzed the expression pattern of TFs in DEGs during the anther development (Figure 7B; Supplementary Table S20).…”
Section: Screening Of Important Genes Related To Anthers Developmentmentioning
confidence: 99%